Lateral meniscus root avulsion increases contact pressures: A Finite Element study - Peña Trabalón, Alejandro; Moreno-Vegas, Salvador; Estébanez-Campos, María Belén; Prado-Novoa, María; Espejo-Reina, Alejandro; García-Vacas, Francisco; Pérez-Blanca, Ana (My University, 2022)
Deleterious consequences of posterior meniscal root detachment have been related to variations in contact pressure distribution seen in biomechanical investigations. However, little is known about the biomechanical effects of lateral anterior root avulsions, despite clinical studies reporting it as a lesion concomitant with anterior cruciate ligament injuries and tibial fractures and as an iatrogenic injury during anterior cruciate ligament reconstructions. This work analyzes variations in contact pressure due to lateral meniscus anterior root avulsion using a knee finite element model.
Keywords: Meniscos; Lateral Meniscus; Anterior root avulsion; Biomechanics; Finite Element Model